Life Cycle Design and Assessment of an Algal Biofuel that is Sustainable, Scalable, and Salable - Orfield, Nolan D.; University of Michigan. (2013)
is incorporated into an analysis that models the performance of an algal biorefinery. Results demonstrate a design trade-off, as the reaction conditions for minimizing the carbon footprint (0.74 kg CO2e at 250 °C, 60 minutes) are different than those found for minimizing cost ($1.72/L at 400 °C, 5 minutes). A novel regrowth pathway featuring utilization of E. coli to boost oil yields is also explored. It was found that the pathway could further reduce costs but comes with an increased carbon footprint and reduced net energy ratio.
Dissertation (Ph.D.)--University of Michigan.
Includes bibliographical references.
is incorporated into an analysis that models the performance of an algal biorefinery. Results demonstrate a design trade-off, as the reaction conditions for minimizing the carbon footprint (0.74 kg CO2e at 250 °C, 60 minutes) are different than those found for minimizing cost ($1.72/L at 400 °C, 5 minutes). A novel regrowth pathway featuring utilization of E. coli to boost oil yields is also explored. It was found that the pathway could further reduce costs but comes with an increased carbon footprint and reduced net energy ratio.
Results of the analysis highlight the inability to scale beyond 1.7 billion liters annually due primarily to the limited availability of nutrients in wastewater. Growing heterotrophic algae in fermenters with sugar as the energy and carbon source rather than sunlight and carbon dioxide is an approach being pursued in the private sector. Results of this study indicate that a reduction in the global warming potential and an improvement in the fossil energy ratio for algal biodiesel could be possible for the heterotrophic pathway relative to the phototrophic, but only if fermentation can be performed efficiently. The sugar crops used as feedstocks for heterotrophic cultivation require more land, however, and introduce concerns about land constraints. Lastly, a life cycle assessment of an algal biorefinery featuring hydrothermal liquefaction is conducted. Recent experimental work providing insight into the HTL reaction networks
Algae are an appealing source of bioenergy due to their high yields relative to terrestrial energy crops. The high cost of production, however, has prohibited commercialization despite significant investment by the private sector. Three novel strategies and technologies encompassing algae production and conversion have been examined in terms of their life cycle environmental impacts and potential to achieve large scale production. Coupling algae cultivation ponds with flue gas emissions from power utilities to provide carbon dioxide and municipal wastewater to provide nutrients not only reduces the upstream impacts and costs associated with providing inputs, but also provides a credit for wastewater treatment. A geospatial economic overlay analysis was conducted to evaluate the abundance and relative location of the input resources of this co-utilization strategy.
Keywords: Algae.; Biofuel.; Life cycle assessment.; Resource assessment.; Geographic information sciences.; Techno-economic modeling.